Hurricane induced changes in the ocean ecosystem with a coupled physical-biogeochemical model - Arcamone, Roberto (Alma Mater Studiorum - Università di Bologna, 2021)
A thesis work is presented in which a coupled model of physics and biogeochemistry, BFM17-POM1D, is used in order to simulate the ocean dynamics in two areas of the Sargasso Sea and describe the impact of a hurricane on the marine ecosystem. The biogeochemical model tracks 17 state variables, divided into five living functional groups: phytoplankton, zooplankton, dissolved and particulate organic matter, and finally the nutrients. We focus our attention on the evolution of nutrients and oxygen in order to understand how variations in the physical forcing can change the concentrations in both time and depth. The model is spatially one dimensional (1D) and time dependent and the physical forcings are imposed in the whole water column except for the turbulent mixing coefficients that are calculated by a turbulence closure model. No lateral exchange of biochemical tracers is considered. So in order to understand the ocean ecosystem dynamics in two different locations in the North Atlantic subtropical gyre we used different temperature and salinity monthly mean profiles, different wind stress components and general circulation vertical velocity profiles. We tried also to understand the role of biochemical processes characterizing the marine ecosystem, nitrification and particulate remineralization rates, testing how the concentrations are changing for the case without and with the hurricane. Finally, the results are consistent with the expectations: after the passage of a hurricane nutrinets are upwelled and the subsurface chlorophyll maxima attains greater values as well as it is located closer to the surface layer.